Determinants of Carbon Emissions Disclosure in Basic And Chemical Industry Companies: A moderating role of Board of Commissioners Size - Nelly Fatmawati Simamora; Sri Mulyani (Journal of Accounting Auditing and Business, 2023)
Disclosure of carbon emissions in the financial statements of basic industrial and chemical companies is a form of company participation in reducing environmental impacts, especially air pollution. However, not all companies in the industry have fully disclosed their carbon emissions. Only about 17% have disclosed their carbon emissions. This study aims to obtain empirical evidence on whether leverage, firm size, profitability, and institutional ownership affect the disclosure of carbon emissions. Also, to obtain evidence of whether the size of the board of commissioners moderates the relationship between these variables to the disclosure of carbon emissions. The sample for this study were companies in the basic and chemical industry listed on the Indonesia Stock Exchange in 2015-2020, 13 companies were selected purposively. The results showed that leverage and firm size had a positive and significant effect, while profitability had a positive but insignificant effect on the disclosure of carbon emissions. However, institutional ownership negatively and significantly affects the disclosure of carbon emissions. The size of the board of commissioners moderates the influence of leverage on the disclosure of carbon emissions in a negative and significant direction. As for the effect of profitability on the disclosure of carbon emissions, the size of the board of commissioners moderates insignificantly.